Mechanistic Investigations into Catalytic Wittig Reactions - Ficarra, Filippo (2023)
Catalytic Wittig reactions present a versatile organocatalytic approach to olefin synthesis reducing the problematic waste associated with the classic Wittig reaction. Although this chemistry has been known for over a decade it has not seen use beyond academic research. In this thesis we aim to address the limitations associated with this chemistry. We present a new less hazardous route to the phosphine oxides employed in catalytic Wittig reactions. We then present our initial results conducting the first kinetic study of this chemistry. Finally computational screening of phosphine oxides gives insight on the optimal catalyst structure to lower the energy barrier in the rate limiting reduction.